A Survey on Data Security in cloud using ECC - Bharath L, Mohan Kumar TG , Sanjay H A, Somashekara S N (International Journal of Advanced Science and Technology, 2020)
Demand for cloud computing as a utility is enormously increasing. Cloud computing offers a vast amount of memory sufficient to serve most of the users using it since cloud computing has a distributed approach. Security becomes the primary concern, for which security protocols have to be implemented. The Kerberos authentication protocol, was once the most secured protocol to meet the security requirements. Many authors have thereby improvised the same, consequently producing a more effective public-key cryptography referred to as RSA cryptography. The RSA cryptography is referred to as efficient but it has some pitfalls. To resolve the pitfalls, the Elliptic curve cryptography has come into picture. The proposed model uses Kerberos authentication protocol with Elliptic curve cryptography to meet security requirements, and also provides other benefits like reduction in cost, memory usage in cloud.